Circadian Rhythms and Sleep Are Dependent Upon Expression Levels of Key Ubiquitin Ligase Ube3a - Shi, Shu-qun; Mahoney, Carrie E.; Houdek, Pavel; Zhao, Wenling; Anderson, Matthew P.; Zhuo, Xinming; Beaudet, Arthur; Sumova, Alena; Scammell, Thomas E.; Johnson, Carl Hirschie (Frontiers in Behavioral Neuroscience, 2022)
Normal neurodevelopment requires precise expression of the key ubiquitin ligase gene Ube3a . Comparing newly generated mouse models for Ube3a downregulation (models of Angelman syndrome) vs. Ube3a upregulation (models for autism), we find reciprocal effects of Ube3a gene dosage on phenotypes associated with circadian rhythmicity, including the amount of locomotor activity. Consistent with results from neurons in general, we find that Ube3a is imprinted in neurons of the suprachiasmatic nuclei (SCN), the pacemaking circadian brain locus, despite other claims that SCN neurons were somehow exceptional to these imprinting rules. In addition, Ube3a -deficient mice lack the typical drop in wake late in the dark period and have blunted responses to sleep deprivation. Suppression of physical activity by light in Ube3a -deficient mice is not due to anxiety as measured by behavioral tests and stress hormones; quantification of stress hormones may provide a mechanistic link to sleep alteration and memory deficits caused by Ube3a deficiency, and serve as an easily measurable biomarker for evaluating potential therapeutic treatments for Angelman syndrome. We conclude that reduced Ube3a gene dosage affects not only neurodevelopment but also sleep patterns and circadian rhythms.